Compromises in career-related decisions: Examining the role of compromise severity - WEE, Serena Ghin Hee (Institutional Knowledge at Singapore Management University, 2014)
This study tested L. S. Gottfredson’s (1996) revised compromise theory by examining whether the relative importance of job sex type, job prestige, and person–job interest congruence for predicting job choice changed as the level of compromise required changed. The fully within-persons design had participants engage in a simulated occupational choice task where job sex type and job prestige were manipulated to be experimentally independent. Participants 1st categorized jobs as unacceptable, acceptable, or preferred. Then, within each category, they made further pairwise choices among jobs in that category. In Study 1, participants were 168 college seniors (124 women, 44 men) from a large Midwestern university. In Study 2, participants were 262 (146 women, 116 men) individuals residing in the United States and recruited via Amazon’s Mechanical Turk platform. Across both studies, job sex type predicted choice when large compromises were required. Across both studies, job prestige did not predict choice when moderate compromises were required. In Study 2 but not Study 1, person–job interest congruence predicted choice when minimal compromises were required.